Determinación de parámetros eléctricos de motores y generadores Ac y Dc en el módulo Lab Volt - Cabay Borja, Santiago Javier (2022)
This thesis project determines the electrical parameters in AC and DC motors and generators in the LabVolt module, which focuses on electric motors and generators' fundamental operating principles of alternating current and direct current. It is designed for training and practical learning with electrical machines, capacitive, resistive, inductive loads, and measuring instruments such as voltmeter, ammeter, tachometer. This study allows the acquisition and measurement of electrical parameters such as voltage, current, power, frequency, power factor. For the development of the topic, preventive maintenance of the equipment of the LabVolt module was made. The practices were carried out in the module such as: Electrical power and Power Factor of an motor, the universal motor, The squirrel cage induction motor, The synchronous motor, which were oriented in the technical part in the measurement of electrical parameters. It was made with the capacitor starter motor, universal motor, synchronous motor/generator, four-pole squirrel cage induction motor, external measuring equipment, data, and control interface. This research helped to verify the data obtained, which allows comparing results. The measurements and calculations with the respective equations permit the efficient development of the recording of electrical parameters in motors and generators. The results are presented in the analysis and discussion part. In conclusion, the equipment maintenance helped improve the working conditions with AC and DC motors and generators in the LabVolt module.